Clara Wieck and her Piano Variations: Postclassical Pianism of the 1830s - Tan, Cheryl (Cornell University, 2024)
Scholarly and performative interest in the life and works of Clara Wieck-Schumann (1819–1896) began in the last decades of the twentieth century. The musicological interest in Wieck-Schumann in the four decades since Nancy Reich’s landmark biography (1985) has led to a rich body of scholarship that has examined her numerous identities as a composer, performer, wife, daughter, mother, musical editor, and pedagogue. Much of the existing scholarship has been centred on post-marriage Clara Schumann; by contrast, the early career of Clara Wieck before her marriage in 1840 has received considerably less attention. This dissertation addresses this gap in musical scholarship, focusing on the first decade of Wieck’s career and the postclassical milieu characterizing her childhood. It combines archival work with a study of instruments, aesthetics, culture, and musical analysis to examine the wider culture of postclassical pianism in the 1830s, its repertory, and the ways in which Wieck cultivated and established her image as a virtuosa within this milieu. In bringing together distinct methodological approaches, it seeks first to contextualize the aesthetics of postclassical pianism, then to investigate the genre of postclassical concert variations, both in wider musical culture and their role in Wieck’s programming and performing practices. The genre of postclassical concert variations was pivotal to Wieck’s early career and ubiquitous in wider musical life of the early nineteenth century, but fell to obsolescence by the middle of her career, and has since remained marginalized. Its reception history invites a reflection upon the longstanding historiographical narratives and practices that have come to shape our engagement with this repertoire and the culture of instrumental virtuosity to which it belonged, particularly in the domains of musicology and classical pianism. Engaging with the historical, social, cultural, and performative histories of these works and their composers reveals the rich and diverse practice embodied by this repertoire, and invites a deeper consideration of the complex relationships between gender, pianos, aesthetics, and cultural conceptions of virtuosity.
PUBLISHED
Keywords: HUMANITIES and RELIGION::Aesthetic subjects::Music; Creative Arts Practice; Music history; Musicology/Music Theory; Performance practice